At the intersection of interests: evolving creative processes and new agency-media dynamics. Issue 1 (9th April 2021) - Derda, I.
Abstract: The development of forms at the blurred boundaries between advertising and editorial content has led to a shift in advertising industry practices. In the process of campaign development, it is not uncommon for media platforms to take on some of creative tasks that were once traditionally delivered by advertising agencies. This study investigates how changes in the media landscape have affected creative processes, and identifies a paradigm shift whereby media platforms have become important (or even key) stakeholders in the creative processes. The study also examines the consequences of the parties' approaches to the situation and particularly to working relationships.